Quaternary ammonium salt cationic polymer, preparation method and application thereof, and quaternary ammonium salt cationic surfactant
By using quaternary ammonium cationic polymers and amide monomer compounds in shampoo products, the electrostatic damage caused by anionic surfactants is solved, the combing and smoothness of the hair is improved, and the better anti-static effect is achieved. and security.
Patent Information
- Application Number
- CN202411221112.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-13
AI Technical Summary
Existing shampoo products contain anionic surfactants, causing static electricity on the hair surface, damaging the hair, increasing combing resistance, and poor anti-static effect, resulting in dryness and difficulty in combing.
Quaternary ammonium cationic polymer obtained by radical polymerization, combined with amide monomer compounds and polyfunctional acrylate compounds, to prepare quaternary ammonium cationic surfactants for use in shampoos to improve antistatic effect and hair smoothness. sex.
Significantly improves hair combing and smoothness, reduces friction and static voltage, improves the safety and feel of shampoo, and reduces the risk of dryness and damage to hair.
Smart Images

Figure BDA0005023068410000031 
Figure BDA0005023068410000032 
Figure BDA0005023068410000041
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymers and their applications, and relates to a quaternary ammonium salt cationic polymer, a preparation method and application, and a quaternary ammonium salt cationic surfactant. Background Art
[0002] Shampoo is the most widely used hair care product and one of the most commonly used hair cosmetics. It is used to wash away the oil secreted by the human body, sweat, cells shed from the scalp, foreign dust, microorganisms, residues of styling products and bad odors attached to the scalp and hair, keeping the scalp and hair clean and the hair beautiful.
[0003] Surfactants are one of the main ingredients in shampoo. There are many types of surfactants on the market, and each has its own unique properties. Surfactants can be divided into cationic, anionic, zwitterionic and nonionic, depending on whether they produce ions after dissolving in water. These surfactants are used in shampoo to clean, degrease and foam.
[0004] Reference is made to a Chinese invention patent document with publication number CN110934794A, which discloses a special shampoo for industrial enterprises. The hyaluronic acid contained in the shampoo acts on the epidermis of the skin, forms chemical hydrogen bonds with the skin surface, organizes the loss of nutrients in the epidermis of the skin, and protects the skin. In addition, the sodium dodecyl sulfate component contained therein has good foaming and detergency properties, and can effectively remove tar, wax, dust and other impurities on the hair, and has a good cleaning effect; however, the sulfate component added therein will generate more negative charges after contacting the surface of the hair, and generate static electricity after friction, making the hair more fragile.
[0005] The Chinese invention patent document with reference publication number CN111194207A discloses a compact shampoo composition, which contains sodium cocoyl isethionate, anionic surfactant and zwitterionic surfactant, wherein the anionic surfactant is specifically acyl glutamate. This shampoo substantially free of sulfate-based surfactants can avoid the damage of sulfate to hair and skin (especially dyed hair), and the addition of sodium cocoyl isethionate can bring better cleaning ability and foaming effect to the shampoo. However, the added surfactant is anionic, which generates static electricity after friction, and the hair scales of the hair cuticle layer are more likely to open and curl.
[0006] In summary, the main ingredients of existing shampoo products on the market are mostly anionic surfactants. Although they can play a good cleaning role and produce rich foam, they will cause additional negative charges on the hair surface after use, and then generate static electricity after friction. This static electricity phenomenon will damage the hair, causing some hair cuticles on the hair surface to fall off, and the hair scales will no longer be neatly arranged, thereby increasing the friction coefficient of the hair surface, making it difficult to comb. When the hair is dry or wet, the resistance encountered by the comb when passing through the hair will increase significantly. Therefore, shampoo products containing anionic surfactants have poor anti-static effects and are prone to causing dry hair and difficulty in combing. Summary of the invention
[0007] Aiming at the technical problem that the above-mentioned anionic surfactant shampoo products have poor antistatic effect and easily cause dry hair, the present invention provides a quaternary ammonium salt cationic polymer, a preparation method and application, and a quaternary ammonium salt cationic surfactant.
[0008] The quaternary ammonium salt cationic polymer obtained by free radical polymerization can solve the problems of poor antistatic effect and dry hair existing in shampoo products. Furthermore, the quaternary ammonium salt cationic polymer is compounded with an active agent to obtain a quaternary ammonium salt cationic surfactant, which is better used in shampoo products.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is:
[0010] A quaternary ammonium salt cationic polymer, characterized in that the general structural formula of the quaternary ammonium salt cationic polymer is:
[0011]
[0012] Wherein: R1 is hydrogen or an alkyl group with 1 to 4 carbon atoms, R2 is hydrogen or an alkyl group with 1 to 3 carbon atoms, R3 is an alkyl group with 1 to 6 carbon atoms, and m is an integer of 1 to 5;
[0013] R4 is hydrogen or an alkyl group having 1 to 8 carbon atoms, R5 is hydrogen or an alkyl group having 1 to 9 carbon atoms, R6 is hydrogen or an alkyl group having 2 to 7 carbon atoms, R7 is hydrogen or an alkyl group having 1 to 4 carbon atoms or an alkyl alcohol having 1 to 2 carbon atoms, and n is an integer of 1 to 4;
[0014] R8 is hydrogen or an alkyl group having 1 to 2 carbon atoms or an alkyl alcohol having 1 to 2 carbon atoms, R9 is hydrogen or an alkyl group having 1 to 3 carbon atoms; R 10 is hydrogen or an alkyl group of 2 to 4 carbon atoms, R 11 is hydrogen or an alkyl group having 2 to 6 carbon atoms, R 12 is hydrogen or an alkyl group having 1 to 5 carbon atoms or an alkyl alcohol having 1 to 3 carbon atoms.
[0015] It is further defined that the quaternary ammonium salt cationic polymer is polymerized by 10 wt % to 60 wt % of a quaternary ammonium acrylate compound, 1 wt % to 15 wt % of a multifunctional acrylate compound and 30 wt % to 89 wt % of an amide monomer compound.
[0016] It is further defined that the structural formula of the quaternary ammonium acrylate compound is:
[0017]
[0018] Wherein: R1 is hydrogen or an alkyl group with 1 to 4 carbon atoms, R2 is hydrogen or an alkyl group with 1 to 3 carbon atoms, R3 is an alkyl group with 1 to 6 carbon atoms, and m is an integer of 1 to 5;
[0019] The structural formula of the multifunctional acrylate compound is:
[0020]
[0021] Wherein: R4 is hydrogen or an alkyl group of 1-8 carbon atoms, R5 is hydrogen or an alkyl group of 1-9 carbon atoms, R6 is hydrogen or an alkyl group of 2-7 carbon atoms, R7 is hydrogen or an alkyl group of 1-4 carbon atoms or an alkyl alcohol of 1-2 carbon atoms, and n is an integer of 1-4;
[0022] The structural formula of the amide monomer compound is:
[0023]
[0024] Wherein: R8 is hydrogen or an alkyl group with 1-2 carbon atoms or an alkyl alcohol with 1-2 carbon atoms, R9 is hydrogen or an alkyl group with 1-3 carbon atoms; R 10 is hydrogen or an alkyl group of 2 to 4 carbon atoms, R 11 is hydrogen or an alkyl group having 2 to 6 carbon atoms, R 12 is hydrogen or an alkyl group having 1 to 5 carbon atoms or an alkyl alcohol having 1 to 3 carbon atoms.
[0025] The preparation method of the quaternary ammonium salt cationic polymer as described above comprises the following steps:
[0026] S1, synthetic quaternary ammonium acrylate compound;
[0027] S2, dissolving a quaternary ammonium acrylate compound in a solvent, adding a multifunctional acrylate compound, an amide monomer compound and a chain transfer agent, wherein the amount of the chain transfer agent is 0.01wt% to 0.5wt%, and stirring to form a monomer solution;
[0028] S3. Under N2 protection conditions, add the initiator solution dropwise to the monomer solution, control the reaction temperature to 50°C-80°C, the reaction time to 2h-5h, the stirring speed to 150RPM-300RPM, and the dropping acceleration to 1mL / min-10mL / min to obtain a quaternary ammonium salt cationic polymer.
[0029] It is further defined that in step S1, the quaternary ammonium acrylate compound is synthesized from compound 1 and compound 2 in a molar ratio of 1:1, and the structural formula of compound 1 is The structural formula of the compound 2 is
[0030] Wherein: R1 is hydrogen or an alkyl group with 1-4 carbon atoms, R2 is hydrogen or an alkyl group with 1-3 carbon atoms, R3 is an alkyl group with 1-6 carbon atoms, and m is an integer of 1-5.
[0031] It is further defined that the synthesis process of the quaternary ammonium acrylate compound is: adding compound 2 dropwise into compound 1, starting stirring at room temperature, and after the dropwise addition is completed, controlling the reaction temperature to 50°C-60°C, and the reaction time to 1h-3h to obtain the quaternary ammonium acrylate compound.
[0032] It is further defined that in step S3, the initiator solution is obtained by dissolving an initiator in a solvent; the initiator is hydrogen peroxide, sodium persulfate, potassium persulfate or ammonium persulfate, and the amount of the initiator used is 2wt% to 8wt% of the total amount of the monomer solution.
[0033] A quaternary ammonium salt cationic surfactant comprises a cationic polymer and an active agent B; the active agent B accounts for 0.1wt% to 10wt% in the quaternary ammonium salt cationic surfactant; and the cationic polymer is the quaternary ammonium salt cationic polymer.
[0034] It is further defined that the active agent B is at least one of guar gum, cocamide, carbomer, AES60, propylene glycol, ethylene glycol, glycerol, polyethylene glycol 4000, polyethylene glycol 6000, polyethylene glycol 8000 and polyacrylamide.
[0035] Application of the quaternary ammonium salt cationic polymer in hair shampooing and hair care.
[0036] Compared with the traditional technology, the beneficial effects of the present invention are:
[0037] 1. The present invention uses amide monomer compounds, quaternary ammonium acrylate compounds and multifunctional acrylate compounds as raw materials, and obtains a new type of quaternary ammonium salt cationic polymer through free radical polymerization, which can solve the problems of poor antistatic effect and dry hair existing in shampoo products, and has a better softening effect.
[0038] 2. The novel quaternary ammonium salt cationic polymer provided by the present invention, which contains an amide monomer compound, is milder in composition, safer and less risky than the common products on the market that use acrylamide as a starting material. This is because acrylamide monomer has neurotoxicity, carcinogenicity and teratogenicity, can pass through the skin and gastrointestinal tract, and then cause various systemic reactions. Acrylamide is listed as a possible human carcinogen, so acrylamide has a higher risk for human safety.
[0039] 3. The quaternary ammonium salt cationic polymer of the present invention has a high viscosity performance, which can reach 6581mPa·S to 10685mPa·S. When used in shampoo, it has a high compounding effect; the pH of the quaternary ammonium salt cationic polymer is weakly acidic, and weak acidity is more in line with the acidic characteristics of the human body, and has a better sense of use than alkalinity. Therefore, the quaternary ammonium salt cationic polymer of the present invention can be better used in shampoo products.
[0040] 4. The present invention has found through testing that the maximum combing work of the quaternary ammonium salt cationic polymer used in shampoo products reaches 0.02J-0.06J, the maximum friction force is 1.51N-1.68N, and the maximum static voltage is 1.53KV-1.75KV. The above three performance indicators are significantly lower than the corresponding performance indicators of existing commercial shampoos, indicating that the cationic shampoo formed by the polymer of the present invention has a significant effect in improving the combing property of hair, increasing the smoothness of the hair surface, and improving the antistatic property of hair.
[0041] 5. In the present invention, a quaternary ammonium salt cationic polymer and an active agent are used to form a quaternary ammonium salt cationic surfactant, which can achieve thickening and foaming effects, thereby improving the use effect of the quaternary ammonium salt cationic polymer. DETAILED DESCRIPTION
[0042] The technical solution protected by the present invention is now described in detail in conjunction with the embodiments. However, it is obvious that the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the described embodiments of the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0043] The invention provides a quaternary ammonium salt cationic polymer, which is polymerized by the following weight fractions: 10% to 60% of a quaternary ammonium acrylate compound, 1% to 15% of a multifunctional acrylate compound and 30% to 89% of an amide monomer compound.
[0044] In this embodiment, the quaternary ammonium acrylate compound has the following structural formula:
[0045]
[0046] Wherein: R1 is hydrogen or an alkyl group with 1-4 carbon atoms, R2 is hydrogen or an alkyl group with 1-3 carbon atoms, R3 is an alkyl group with 1-6 carbon atoms, and m is an integer of 1-5.
[0047] The structural formula of the multifunctional acrylate compound is as follows:
[0048]
[0049] R4 is hydrogen or an alkyl group having 1-8 carbon atoms, R5 is hydrogen or an alkyl group having 1-9 carbon atoms, R6 is hydrogen or an alkyl group having 2-7 carbon atoms, R7 is hydrogen or an alkyl group having 1-4 carbon atoms or an alkyl alcohol having 1-2 carbon atoms, and n is an integer of 1-4.
[0050] The structural formula of amide monomer compounds is as follows
[0051]
[0052] Wherein: R8 is hydrogen or an alkyl group with 1-2 carbon atoms or an alkyl alcohol with 1-2 carbon atoms, R9 is hydrogen or an alkyl group with 1-3 carbon atoms; R 10 is hydrogen or an alkyl group of 2 to 4 carbon atoms, R 11 is hydrogen or an alkyl group having 2 to 6 carbon atoms, R 12 is hydrogen or an alkyl group having 1 to 5 carbon atoms or an alkyl alcohol having 1 to 3 carbon atoms.
[0053] In the present invention: the general structural formula of the quaternary ammonium salt cationic polymer is:
[0054]
[0055] The present invention also provides a method for preparing a quaternary ammonium salt cationic polymer, comprising the following steps:
[0056] S1, synthetic quaternary ammonium acrylate compound;
[0057] In step S1 of the present invention, compound 1 and compound 2 are reacted in a molar ratio of 1:1, compound 2 is added dropwise to compound 1, and stirring is started at room temperature. After the dropwise addition is completed, the reaction temperature is controlled to 50° C.-60° C., and the reaction time is 1 h-3 h to obtain a quaternary ammonium acrylate compound.
[0058] The specific synthetic route is as follows:
[0059]
[0060] Wherein: 1 is the structural formula of compound 1; 2 is the structural formula of compound 2; 3 is the structural formula of quaternary ammonium acrylate compound.
[0061] Wherein: R1 is hydrogen or an alkyl group with 1-4 carbon atoms, R2 is hydrogen or an alkyl group with 1-3 carbon atoms, R3 is an alkyl group with 1-6 carbon atoms, and m is an integer of 1-5.
[0062] S2. Dissolve the quaternary ammonium acrylate compound in a solvent, add an amide monomer compound, a multifunctional acrylate compound and a chain transfer agent, wherein the amount of the chain transfer agent is 0.01 wt % to 0.5 wt %, and stir to form a monomer solution.
[0063] S3. Under N2 protection conditions, add the initiator solution dropwise to the monomer solution, control the reaction temperature to 50°C-80°C, the reaction time to 2h-5h, the stirring speed to 150RPM-300RPM, and the dropwise addition rate to 1mL / min-10mL / min to obtain a quaternary ammonium salt cationic polymer.
[0064] The synthetic route of quaternary ammonium salt cationic polymer is as follows:
[0065]
[0066] Wherein: 3 is the structural formula of a quaternary ammonium acrylate compound, 4 is the structural formula of a multifunctional acrylate compound, and 5 is the structural formula of an amide monomer compound.
[0067] In step S3 of the present invention, the initiator solution is obtained by dissolving an initiator in a solvent; the initiator is hydrogen peroxide, sodium persulfate, potassium persulfate or ammonium persulfate, and the amount of the initiator solution is 2wt% to 8wt% of the total amount of the monomer solution.
[0068] The present invention also provides a quaternary ammonium salt cationic surfactant, comprising a cationic polymer and an active agent B; the active agent B accounts for 0.1wt% to 10wt% in the quaternary ammonium salt cationic surfactant; and the cationic polymer is the above-mentioned quaternary ammonium salt cationic polymer.
[0069] In the present invention, the active agent B is at least one of guar gum, cocamide, carbomer, AES60, propylene glycol, ethylene glycol, glycerol, polyethylene glycol 4000, polyethylene glycol 6000 or polyethylene glycol 8000 and polyacrylamide.
[0070] Preferably, the proportion of active agent B in the quaternary ammonium salt cationic surfactant is 0.5 wt % to 7 wt %.
[0071] More preferably, the proportion of the active agent B in the quaternary ammonium salt cationic surfactant is 1 wt% to 4 wt%.
[0072] The quaternary ammonium salt cationic polymer provided by the present invention is used in washing and care products, and in addition to the cleaning effect, it also has the function of caring for hair, improves the dry and wet combing properties of hair, and well solves the problem that traditional anionic shampoo products are prone to static electricity, making hair smooth and shiny, and also has a strong bactericidal effect, effectively cleans the scalp, and achieves the effect of shampooing and hair care.
[0073] The present invention is described in detail below with reference to specific embodiments.
[0074] It should be noted that, unless otherwise specified, the reagents and drugs used in the following examples and experiments are conventional commercially available products.
[0075] It should be noted that, unless otherwise specified, the operations used in the following examples and experiments are routine operations in the art.
[0076] Example 1
[0077] The quaternary ammonium salt cationic polymer provided in this embodiment is polymerized by the following mass fractions: 10% of a quaternary ammonium acrylate compound, 1% of a multifunctional acrylate compound, and 89% of an amide monomer compound.
[0078] In this embodiment, the masses of the quaternary ammonium acrylate compound, the multifunctional acrylate compound and the amide monomer compound are 2.6931 g, 0.6930 g and 11.319 g, respectively.
[0079] In this embodiment, the quaternary ammonium acrylate compound is a quaternary ammonium salt derivative, the multifunctional acrylate compound is 9(ethoxy)trimethylolpropane triacrylate, and the amide monomer compound is N,N-diethylacrylamide.
[0080] In this embodiment, the preparation method of the quaternary ammonium salt cationic polymer comprises the following steps:
[0081] S1. Preparation of quaternary ammonium salt derivatives
[0082] Add dimethylaminoethyl acrylate (85.48 g, 0.597 mol) to a 250 mL round-bottom flask, start stirring at room temperature, and add dimethyl sulfate (75.30 g, 0.597 mol) dropwise. During the addition, the reaction liquid changes from clear to milky white, accompanied by heat release. After the addition is completed, continue stirring and reacting for 2 hours at a water bath temperature of 60°C to obtain a light yellow transparent product, which is a quaternary ammonium salt derivative.
[0083] S2. Weigh the quaternary ammonium salt derivative, 9(ethoxy)trimethylolpropane triacrylate, N,N-diethylacrylamide, and 0.1% chain transfer agent (0.0147 g) separately and dissolve them in 200 mL of pure water to prepare a monomer solution.
[0084] S3, transfer the monomer solvent to a 1L four-necked round-bottom flask, protect with N2, heat to 65°C, stir at 200r / min; keep heating and stirring, continuously drip initiator solution, control the dripping speed to 2.25mL / min, dripping time to 183min. After the dripping is completed, continue heating and reacting for 2h to obtain quaternary ammonium salt cationic polymer.
[0085] In this step, 0.59 g of potassium persulfate was dissolved in 412.71 mL of pure water to prepare an initiator solution, wherein the mass fraction of potassium persulfate was 4% of the total amount of the monomer solution.
[0086] The quaternary ammonium salt cationic polymer prepared in this example is a colorless, transparent, viscous liquid with a characteristic odor, a pH of 3.93, and a viscosity of 6581 mPa·s.
[0087] Example 2
[0088] The quaternary ammonium salt cationic polymer provided in this embodiment is polymerized by the following mass fractions: 60% of a quaternary ammonium acrylate compound, 7% of a multifunctional acrylate compound, and 33% of an amide monomer compound.
[0089] In this embodiment, the masses of the quaternary ammonium acrylate compound, the multifunctional acrylate compound and the amide monomer compound are 16.1589 g, 2.9960 g and 3.3363 g respectively.
[0090] In this embodiment, the quaternary ammonium acrylate compound is a quaternary ammonium salt derivative, the multifunctional acrylate compound is 3 (propoxy) propylene glycol triacrylate, and the amide monomer compound is N-(hydroxymethyl) acrylamide.
[0091] In this embodiment, the preparation method of the quaternary ammonium salt cationic polymer comprises the following steps:
[0092] S1. Preparation of quaternary ammonium salt derivatives
[0093] Add dimethylaminoethyl acrylate (85.48 g, 0.597 mol) to a 250 mL round-bottom flask, start stirring at room temperature, and add dimethyl sulfate (75.30 g, 0.597 mol) dropwise. During the addition, the reaction liquid changes from clear to milky white, accompanied by heat release. After the addition is completed, continue stirring and reacting for 2 hours at a water bath temperature of 60°C to obtain a light yellow transparent product, which is a quaternary ammonium salt derivative.
[0094] S2. Weigh the quaternary ammonium salt derivative, 3 (propoxy) propylene glycol triacrylate, N-(hydroxymethyl) acrylamide, and 0.3% chain transfer agent (0.0675 g) separately and dissolve them in 300 mL of pure water to prepare a monomer solution.
[0095] S3, transfer the monomer solvent to a 1.5L four-necked round-bottom flask, protect with N2, heat to 65°C, stir at 250r / min; keep heating and stirring, continuously drip initiator solution, control the dripping speed to 5mL / min, and drip time to 127.43min. After the dripping is completed, continue heating and reacting for 2h to obtain a quaternary ammonium salt cationic polymer.
[0096] In this step, 0.8996 g of potassium persulfate was dissolved in 637.13 mL of pure water to prepare an initiator solution, wherein the mass fraction of potassium persulfate was 6% of the total amount of the monomer solution.
[0097] The quaternary ammonium salt cationic polymer prepared in this example is a colorless, transparent, viscous liquid with a characteristic odor, a pH of 3.85, and a viscosity of 10685 mPa·s.
[0098] Example 3
[0099] The quaternary ammonium salt cationic polymer provided in this embodiment is polymerized by the following mass fractions: 57% of a quaternary ammonium acrylate compound, 3% of a multifunctional acrylate compound, and 40% of an amide monomer compound.
[0100] In this embodiment, the masses of the quaternary ammonium acrylate compound, the multifunctional acrylate compound and the amide monomer compound are 15.3510 g, 1.5840 g and 0.5087 g respectively.
[0101] In this embodiment, the quaternary ammonium acrylate compound is a quaternary ammonium salt derivative, the multifunctional acrylate compound is 4 (ethoxy) pentaerythritol tetraacrylate, and the amide monomer compound is N, N-diethylacrylamide.
[0102] In this embodiment, the preparation method of the quaternary ammonium salt cationic polymer comprises the following steps:
[0103] S1. Preparation of quaternary ammonium salt derivatives
[0104] Add dimethylaminoethyl acrylate (85.48 g, 0.597 mol) to a 250 mL round-bottom flask, start stirring at room temperature, and add dimethyl sulfate (75.30 g, 0.597 mol) dropwise. During the addition, the reaction liquid changes from clear to milky white, accompanied by heat release. After the addition is completed, continue stirring and reacting for 2 hours at a water bath temperature of 60°C to obtain a light yellow transparent product, which is a quaternary ammonium salt derivative.
[0105] S2. Weigh the quaternary ammonium salt derivative, 4 (ethoxy) pentaerythritol tetraacrylate, N,N-diethylacrylamide, and 0.1% chain transfer agent (0.0174 g) respectively and dissolve them in 240 mL of pure water to prepare a monomer solution.
[0106] S3, transfer the monomer solvent to a 1.5L four-necked round-bottom flask, protect with N2, heat to 65°C, stir at 250r / min; keep heating and stirring, continuously drip initiator solution, control the dripping speed to 2.45mL / min, dripping time to 198min. After the dripping is completed, continue heating and reacting for 2h to obtain quaternary ammonium salt cationic polymer.
[0107] In this step, 1.0466 g of potassium persulfate was dissolved in 486.82 mL of pure water to prepare an initiator solution, wherein the mass fraction of potassium persulfate was 6% of the total amount of the monomer solution.
[0108] The quaternary ammonium salt cationic polymer prepared in this example is a colorless, transparent, viscous liquid with a characteristic odor, a pH of 3.76, and a viscosity of 4875 mPa·s.
[0109] Example 4
[0110] The quaternary ammonium salt cationic polymer provided in this embodiment is polymerized by the following mass fractions: 26% of a quaternary ammonium acrylate compound, 1% of a multifunctional acrylate compound, and 73% of an amide monomer compound.
[0111] In this embodiment, the masses of the quaternary ammonium acrylate compound, the multifunctional acrylate compound and the amide monomer compound are 7.0021 g, 0.4280 g and 9.2841 g, respectively.
[0112] In this embodiment, the quaternary ammonium acrylate compound is a quaternary ammonium salt derivative, the multifunctional acrylate compound is 3 (propoxy) propylene glycol triacrylate, and the amide monomer compound is N, N-diethylacrylamide.
[0113] In this embodiment, the preparation method of the quaternary ammonium salt cationic polymer comprises the following steps:
[0114] S1. Preparation of quaternary ammonium salt derivatives
[0115] Add dimethylaminoethyl acrylate (85.48 g, 0.597 mol) to a 250 mL round-bottom flask, start stirring at room temperature, and add dimethyl sulfate (75.30 g, 0.597 mol) dropwise. During the addition, the reaction liquid changes from clear to milky white, accompanied by heat release. After the addition is completed, continue stirring and reacting for 2 hours at a water bath temperature of 60°C to obtain a light yellow transparent product, which is a quaternary ammonium salt derivative.
[0116] S2. Weigh the quaternary ammonium salt derivative, 3 (propoxy) propylene glycol triacrylate, N, N-diethylacrylamide, and 0.1 wt% of a chain transfer agent (0.0167 g) respectively and dissolve them in 200 mL of pure water to prepare a monomer solution.
[0117] S3, transfer the monomer solvent to a 1.5L four-necked round-bottom flask, protect with N2, heat to 65°C, stir at 230r / min; keep heating and stirring, continuously drip initiator solution, control the dripping speed to 2.10mL / min, dripping time to 236min. After the dripping is completed, continue heating and reacting for 2h to obtain quaternary ammonium salt cationic polymer.
[0118] In this step, 0.3343 g of potassium persulfate was dissolved in 496.43 mL of pure water to prepare an initiator solution, wherein the mass fraction of potassium persulfate was 2% of the total amount of the monomer solution.
[0119] The quaternary ammonium salt cationic polymer prepared in this example is a colorless, transparent, viscous liquid with a characteristic odor, a pH of 3.55, and a viscosity of 3422 mPa·s.
[0120] Example 5
[0121] This embodiment provides a quaternary ammonium salt cationic surfactant, including a cationic polymer and an active agent B.
[0122] In this embodiment, the cationic polymer is the quaternary ammonium salt cationic polymer prepared in Example 1. The active agent B is guar gum.
[0123] In this embodiment, the proportion of the active agent B in the quaternary ammonium salt cationic surfactant is 1 wt %.
[0124] Example 6
[0125] This embodiment provides a quaternary ammonium salt cationic surfactant, including a cationic polymer and an active agent B.
[0126] In this embodiment, the cationic polymer is the quaternary ammonium salt cationic polymer prepared in Example 2. The active agent B is polyethylene glycol 4000.
[0127] In this embodiment, the proportion of the active agent B in the quaternary ammonium salt cationic surfactant is 4 wt %.
[0128] Example 7
[0129] This embodiment provides a quaternary ammonium salt cationic surfactant, including a cationic polymer and an active agent B.
[0130] In this embodiment, the cationic polymer is the quaternary ammonium salt cationic polymer prepared in Example 3. The active agent B is cocamide.
[0131] In this embodiment, the proportion of the active agent B in the quaternary ammonium salt cationic surfactant is 0.5 wt %.
[0132] Example 8
[0133] This embodiment provides a quaternary ammonium salt cationic surfactant, including a cationic polymer and an active agent B.
[0134] In this embodiment, the cationic polymer is the quaternary ammonium salt cationic polymer prepared in Example 4. The active agent B is polyacrylamide.
[0135] In this embodiment, the proportion of the active agent B in the quaternary ammonium salt cationic surfactant is 7 wt %.
[0136] The performance of the quaternary ammonium salt cationic polymer prepared in the example of the present invention was tested. The quaternary ammonium salt cationic polymer provided in the example was used to form a cationic shampoo, and 4 commercially available antistatic shampoos were selected as comparative samples.
[0137] Four cationic shampoos are respectively made from the quaternary ammonium salt cationic polymers in Examples 1 to 4. The components of the cationic shampoo are: quaternary ammonium salt cationic polymers and base materials, the mass ratio of the quaternary ammonium salt cationic polymers is 2% to 6%, and the rest is the base material; the base material includes: 10.5wt% sodium laureth sulfate, 8wt% cocamidopropyl betaine, 1.5wt% polyquaternium-11 and 80wt% water.
[0138] 1. Combing test
[0139] The dynamic hair combing instrument Techno Hashimoto SK-7A was used to conduct detailed tests on the combing properties of 4 cationic shampoos and 4 commercially available shampoos in each step of application, rinsing, wet hair, and dry hair.
[0140] Test principle: The mechanical arm drives the toothed comb to move and comb the hair to evaluate the hair properties. Combability is a test method. The wet hair combing test method is to keep the hair in a wet state, then use a physical property tester connected to a special comb to perform a tensile test (tensile method) to measure the force required when the comb passes through the hair fiber.
[0141] Experimental method: Take 10 hair bundles and number them, first use a detergent to uniformly clean the hair bundles, then divide the 10 hair bundles into 8 groups, and pre-treat the hair bundles with 4 cationic shampoos and 4 commercially available shampoo samples respectively under constant temperature and humidity conditions, fix the hair bundles on the instrument device, wet them and apply the samples, first test the combing force after application; then rinse the hair bundles, and test the combing force after rinsing; after the test, squeeze out the water and test the combing force under wet hair condition; then wait for the hair to be completely dried, and test the combing force under dry hair condition; each hair bundle is tested 3 times, and the average value is taken. The test results are shown in Table 1 below.
[0142] Table 1 Combing test results
[0143] Sample name Example 1 Example 2 Example 3 Example 4 Shampoo A Shampoo B Shampoo C Shampoo D Sample No. Maximum power (J) Maximum power (J) Maximum power (J) Maximum power (J) Maximum power (J) Maximum power (J) Maximum power (J) Maximum power (J) 1 0.05 0.05 0.04 0.02 0.14 0.13 0.15 0.17 2 0.06 0.04 0.03 0.04 0.12 0.11 0.16 0.14 3 0.04 0.03 0.04 0.03 0.14 0.13 0.12 0.13 4 0.06 0.04 0.05 0.06 0.15 0.14 0.14 0.15 5 0.03 0.03 0.03 0.02 0.11 0.12 0.13 0.14 6 0.05 0.05 0.06 0.03 0.16 0.09 0.15 0.16 7 0.04 0.04 0.04 0.05 0.12 0.16 0.12 0.13 8 0.03 0.03 0.05 0.04 0.15 0.11 0.16 0.14 9 0.02 0.03 0.03 0.02 0.16 0.15 0.14 0.12 10 0.04 0.05 0.04 0.03 0.11 0.13 0.12 0.15 average value 0.04 0.04 0.04 0.03 0.14 0.13 0.14 0.14
[0144] As can be seen from Table 1, the maximum combing work of the hair samples treated with the cationic shampoos prepared in Examples 1-4 is 0.02-0.06 J, which is significantly lower than the maximum combing work of the hair samples treated with four commercially available antistatic shampoos, indicating that cationic shampoo has the effect of improving the combing properties of hair.
[0145] 2. Friction test
[0146] Test principle: The friction of hair is one of the commonly used parameters for evaluating the smoothness of hair products. When hair is damaged by physical or chemical treatment, the loss of liposomes, the loss or curling of hair scales will cause the hair surface to become rough, thereby increasing the friction of the hair and reducing the surface smoothness. This method uses a dynamometer to test the friction coefficient, average friction and friction work of the hair bundle before and after the use of the product, and measures the effectiveness of the sample in improving the smoothness of the hair surface by the significant degree of reduction in the friction coefficient, average friction and friction work of the hair bundle.
[0147] The specific test method is:
[0148] (1) Take 10 hair bundles and number them respectively, then divide each hair bundle into 8 groups, and use the cationic shampoo prepared in Example 1 to Example 4 and 4 commercially available shampoo samples to pre-treat the hair bundles for use. (2) Use a dynamometer to test the maximum friction force of the samples and take the average value, and record the test results in Table 2.
[0149] Table 2 Friction performance test results of different test samples
[0150]
[0151] As can be seen from Table 2, the maximum friction force of the hair samples treated with the cationic shampoos prepared in Examples 1-4 is 1.51-1.68N, which is less than the friction force of the hair samples treated with four commercially available antistatic shampoos, indicating that adding the cationic shampoos of the examples has the effect of improving the friction force of the hair and increasing the smoothness of the hair surface.
[0152] 3. Antistatic performance test
[0153] The test method refers to the patent document of publication number CN112213373A, which is a test method for the antistatic performance of hair care products. The static voltage on the hair surface is measured by simulating the action of combing hair in daily life and passing the comb through the hair bundle at a constant speed.
[0154] Specific test method:
[0155] (1) Take 10 hair bundles, number them respectively, and then divide each hair bundle into 8 groups. Use sodium dodecyl sulfate solution (mass concentration is 10%) to wash and dry the hair bundles, and transfer the hair bundles to a constant temperature and humidity environment for 12 hours.
[0156] (2) Using a dynamic combing performance tester, move a mechanical comb through the hair bundle at a constant speed V (V = 100 mm / s-200 mm / s), from the hair root to the hair end, and record the electrostatic voltage on the hair surface at the moment the mechanical comb leaves the hair bundle, which is used as the electrostatic voltage on the hair surface before using the product.
[0157] (3) Then, cationic shampoo and four commercially available shampoo samples were applied to the surface of the hair bundles, and the hair bundles were rinsed after being rubbed to produce foam for 1 minute. After the hair was completely dried, the hair bundles were transferred to a constant temperature and humidity environment for 12 hours for equilibrium before use.
[0158] (4) Repeat step (2) to measure the static voltage on the surface of the hair bundle after using the hair care product.
[0159] (5) Compare the changes in the electrostatic voltage on the hair surface at the moment the mechanical comb leaves the hair bundle before and after using the same product to determine the antistatic efficacy of the product.
[0160] The test results are recorded in Table 3.
[0161] Table 3 Antistatic performance test results
[0162]
[0163] As can be seen from Table 3, the maximum static voltage of the hair samples treated with the cationic shampoos prepared in Examples 1-4 is 1.53-1.75 KV, which is lower than the maximum static voltage of the hair samples treated with four commercially available antistatic shampoos, indicating that adding the cationic shampoos of the examples has the effect of improving the antistatic property of the hair.
[0164] 4. Adjustment comparison
[0165] Three evaluators who had received uniform training were selected to conduct subjective evaluations on the combing properties, feel, gloss, etc. of the cationic shampoos prepared in Examples 1-4 and four commercially available shampoos under the same conditions. The conditioning grades were divided into 1-10. The test results are shown in Table 4.
[0166] Table 4 Results of conditioning grade classification
[0167]
[0168]
[0169] It can be seen from the above combing test values that the cationic shampoo product adding the embodiment foams faster and has dense foam. After drying, the hair will be smoother and more fluffy, without entanglement, and very easy to comb; while the other four antistatic shampoos will have a strong film feeling after drying, and the hair will be rough, dry and easy to tangle, and the combing resistance is strong.
[0170] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A quaternary ammonium salt cationic polymer, characterized in that: The general structural formula of the quaternary ammonium salt cationic polymer is: Wherein: R1 is hydrogen or an alkyl group with 1 to 4 carbon atoms, R2 is hydrogen or an alkyl group with 1 to 3 carbon atoms, R3 is an alkyl group with 1 to 6 carbon atoms, and m is an integer of 1 to 5; R4 is hydrogen or an alkyl group having 1 to 8 carbon atoms, R5 is hydrogen or an alkyl group having 1 to 9 carbon atoms, R6 is hydrogen or an alkyl group having 2 to 7 carbon atoms, R7 is hydrogen or an alkyl group having 1 to 4 carbon atoms or an alkyl alcohol having 1 to 2 carbon atoms, and n is an integer of 1 to 4; R8 is hydrogen or an alkyl group having 1 to 2 carbon atoms or an alkyl alcohol having 1 to 2 carbon atoms, R9 is hydrogen or an alkyl group having 1 to 3 carbon atoms; R 10 is hydrogen or an alkyl group of 2 to 4 carbon atoms, R 11 is hydrogen or an alkyl group having 2 to 6 carbon atoms, R 12 is hydrogen or an alkyl group having 1 to 5 carbon atoms or an alkyl alcohol having 1 to 3 carbon atoms.
2. The quaternary ammonium salt cationic polymer according to claim 1, characterized in that The quaternary ammonium salt cationic polymer is polymerized by 10 wt% to 60 wt% of a quaternary ammonium acrylate compound, 1 wt% to 15 wt% of a multifunctional acrylate compound and 30 wt% to 89 wt% of an amide monomer compound.
3. The quaternary ammonium salt cationic polymer according to claim 2, characterized in that The structural formula of the quaternary ammonium acrylate compound is: Wherein: R1 is hydrogen or an alkyl group with 1 to 4 carbon atoms, R2 is hydrogen or an alkyl group with 1 to 3 carbon atoms, R3 is an alkyl group with 1 to 6 carbon atoms, and m is an integer of 1 to 5; The structural formula of the multifunctional acrylate compound is: Wherein: R4 is hydrogen or an alkyl group of 1-8 carbon atoms, R5 is hydrogen or an alkyl group of 1-9 carbon atoms, R6 is hydrogen or an alkyl group of 2-7 carbon atoms, R7 is hydrogen or an alkyl group of 1-4 carbon atoms or an alkyl alcohol of 1-2 carbon atoms, and n is an integer of 1-4; The structural formula of the amide monomer compound is: Wherein: R8 is hydrogen or an alkyl group with 1-2 carbon atoms or an alkyl alcohol with 1-2 carbon atoms, R9 is hydrogen or an alkyl group with 1-3 carbon atoms; R 10 is hydrogen or an alkyl group of 2 to 4 carbon atoms, R 11 is hydrogen or an alkyl group having 2 to 6 carbon atoms, R 12 is hydrogen or an alkyl group having 1 to 5 carbon atoms or an alkyl alcohol having 1 to 3 carbon atoms.
4. The method for preparing a quaternary ammonium salt cationic polymer according to claim 2, wherein: The preparation method comprises the following steps: S1, synthetic quaternary ammonium acrylate compound; S2, dissolving a quaternary ammonium acrylate compound in a solvent, adding a multifunctional acrylate compound, an amide monomer compound and a chain transfer agent, wherein the amount of the chain transfer agent is 0.01wt% to 0.5wt%, and stirring to form a monomer solution; S3. Under N2 protection conditions, add the initiator solution dropwise to the monomer solution, control the reaction temperature to 50°C-80°C, the reaction time to 2h-5h, the stirring speed to 150RPM-300RPM, and the dropping acceleration to 1mL / min-10mL / min to obtain a quaternary ammonium salt cationic polymer.
5. The preparation method according to claim 4, characterized in that: In step S1, the quaternary ammonium acrylate compound is synthesized from compound 1 and compound 2 in a molar ratio of 1:1, and the structural formula of compound 1 is The structural formula of the compound 2 is Wherein: R1 is hydrogen or an alkyl group with 1-4 carbon atoms, R2 is hydrogen or an alkyl group with 1-3 carbon atoms, R3 is an alkyl group with 1-6 carbon atoms, and m is an integer of 1-5.
6. The preparation method according to claim 5, characterized in that: The synthesis process of the quaternary ammonium acrylate compound is: adding compound 2 dropwise into compound 1, starting stirring at room temperature, and after the dropwise addition is completed, controlling the reaction temperature to 50° C.-60° C., and the reaction time to 1 h-3 h, to obtain the quaternary ammonium acrylate compound.
7. The preparation method according to claim 4, characterized in that: In step S3, the initiator solution is obtained by dissolving an initiator in a solvent; the initiator is hydrogen peroxide, sodium persulfate, potassium persulfate or ammonium persulfate, and the amount of the initiator used is 2wt% to 8wt% of the total amount of the monomer solution.
8. A quaternary ammonium salt cationic surfactant, characterized in that It comprises a cationic polymer and an active agent B; the active agent B accounts for 0.1wt% to 10wt% in the quaternary ammonium salt cationic surfactant; and the cationic polymer is the quaternary ammonium salt cationic polymer according to any one of claims 1 to 3.
9. The quaternary ammonium salt cationic surfactant according to claim 7, characterized in that The active agent B is at least one of guar gum, cocamide, carbomer, AES60, propylene glycol, ethylene glycol, glycerol, polyethylene glycol 4000, polyethylene glycol 6000, polyethylene glycol 8000 and polyacrylamide.
10. Use of the quaternary ammonium salt cationic polymer according to claim 3 in hair shampooing and hair care.
Citation Information
Patent Citations
Shampoo special for industrial enterprises
CN110934794A
Compact shampoo composition containing sulfate-free surfactants
CN111194207A
Method for quickly detecting antistatic property of hair washing and caring product
CN112213373A
